2018
DOI: 10.1038/s41590-018-0254-4
|View full text |Cite
|
Sign up to set email alerts
|

TCF-1 and HEB cooperate to establish the epigenetic and transcription profiles of CD4+CD8+ thymocytes

Abstract: Thymocyte development requires a complex orchestration of multiple factors. Ablating either Tcf-1 or HEB in CD4+CD8+-thymocytes elicits similar developmental outcomes including increased proliferation, decreased survival, and reduced late Tcra rearrangements. Here, we provide a mechanistic explanation for these similarities by showing that Tcf-1 and HEB share ~7000 DNA binding-sites genome- wide and promote chromatin accessibility. The binding of both Tcf-1 and HEB is required at these shared sites for epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 62 publications
(95 reference statements)
5
47
0
Order By: Relevance
“…This acute role in viability complicates identification of direct target genes, but TCF1 positively regulates Gata3, Bcl11b, the DN2 stage marker gene Il2ra (CD25), and genes encoding vital TCR complex and signaling components in early DN cells (Weber et al 2011). Later, in DP stage cells, TCF1 plays a key role to collaborate with and stabilize E proteins (Emmanuel et al 2018) and participates in many effector specialization choices (Steinke et al 2014). Although TCF1 used in Tcell development is the same factor that can mediate Wnt signaling in other developmental contexts, in early T-cell specification, it does not appear to be transducing Wnt signals, since most evidence indicates that TCF1, but not β-catenin or γ-catenin (plakoglobin), is needed in the developing lymphocytes themselves, and deletion of the β-catenin interaction domain of TCF1 does not prevent it from supporting developmental progression (Jeannet et al 2008;Weber et al 2011;Xu et al 2017).…”
Section: Tcf1 and Gata3mentioning
confidence: 99%
See 1 more Smart Citation
“…This acute role in viability complicates identification of direct target genes, but TCF1 positively regulates Gata3, Bcl11b, the DN2 stage marker gene Il2ra (CD25), and genes encoding vital TCR complex and signaling components in early DN cells (Weber et al 2011). Later, in DP stage cells, TCF1 plays a key role to collaborate with and stabilize E proteins (Emmanuel et al 2018) and participates in many effector specialization choices (Steinke et al 2014). Although TCF1 used in Tcell development is the same factor that can mediate Wnt signaling in other developmental contexts, in early T-cell specification, it does not appear to be transducing Wnt signals, since most evidence indicates that TCF1, but not β-catenin or γ-catenin (plakoglobin), is needed in the developing lymphocytes themselves, and deletion of the β-catenin interaction domain of TCF1 does not prevent it from supporting developmental progression (Jeannet et al 2008;Weber et al 2011;Xu et al 2017).…”
Section: Tcf1 and Gata3mentioning
confidence: 99%
“…Whereas E-protein activity in normal DN2b-DN3a pro-T cells operates in a context of high Notch signaling, MAP kinase activation may enable E proteins to be degraded in response to signaling from the Notch pathway itself (Nie et al 2003(Nie et al , 2008, which could also contribute to β selection. In DP thymocytes, recent evidence shows that E2A/HEB proteins not only cobind to DNA with TCF1 but are also posttranslationally stabilized by this interaction (Emmanuel et al 2018). This stability can be important to preserve DP viability an extra day or two, long enough to generate certain rare TCRα recombinations that are important for selection to particular fates (D'Cruz et al 2010).…”
Section: Bcl11b and Factors Activated By Commitmentmentioning
confidence: 99%
“…A study of early developing T cells utilizing methods targeting chromatin organization and its accessibility demonstrated that there are two events of abrupt genome-wide changes – during T cell lineage commitment from DN2 to DN3 and during the transition from DN4 to DP stage [ 52 ]. T cell lineage commitment during the transition from DN2 to DN3 is coordinated by the factor BCL11B [ 53 55 ] together with TCF1 which is responsible for setting up the epigenetic landscape [ 56 , 57 ] and likely by other factors [ 58 , 59 ]. Moreover, TCF1 is important in the second wave of chromatin rearrangements during the transition from DN4 thymocytes to DP and SP stages [ 52 , 57 ].…”
Section: Regulation Of Gene Expression In T Cellsmentioning
confidence: 99%
“…77,78 At the DP stage, HEB and E2A directly upregulate Rorc (RORγt), and HEB collaborates with Tcf7 (TCF1) to regulate a large suite of genes involved in T cell activation and survival. 79,80 They are also needed for proper development of CD4 T cells. 81 Furthermore, E2A and/or HEB regulate many aspects of peripheral αβ T cell differentiation, including the formation of memory CD8 T cells, T-regulatory cells, and Th9 cells.…”
Section: Fe Ats Of S Treng Th: γδ Tc R S I G Naling Titr Ate S E Prmentioning
confidence: 99%
“…E2A binds and upregulates Sox5 and Tcf12 −/− and Tcf7 −/− mice. Rorc is a direct target of HEB activity in DPs, and RORγt and HEB collaborate to upregulate a suite of DP-specific genes, including the pro-survival factor BclXl, encoded by Bcl2l1 80. During γδ T cell development, Rorc is expressed at low levels during Stage 1 and is upregulated in Stage 2 cells entering the γδT17 lineage.…”
mentioning
confidence: 99%